Association of tuberculosis and tricuspid valve endocarditis in AIDS patient with Ebstein heart anomaly - Aleksandra Radovanović Spurnić; Bosiljka Vujisić Tešić; Marija Boričić Kostić; Djordje Jevtović (Journal of Infection in Developing Countries)
A case of tricuspid valve endocarditis in an AIDS patient, an intravenous drug user, initially empirically unsuccessfully treated as a Staphylococcus aureus infection, and thereafter turned to be, most likely, of Mycobacterium tuberculosis etiology is presented.